Land before water: The relative temporal sequence of human alteration of freshwater ecosystems in the conterminous United States. (June 2017) - Wohl, Ellen; Lininger, Katherine B.; Baron, Jill
Abstract: Human alteration of ecosystems prior to Euro-American contact in the area that became the conterminous United States disproportionately affected terrestrial systems compared to freshwater ecosystems, primarily through the use of fire and agriculture in some regions of the United States. After circa 1600 AD, trapping of beaver, along with intensive modification of rivers and wetlands for navigation, mining, flood control, power generation, and agriculture, substantially altered river corridors throughout the country. River corridor here refers to channels of all sizes, from headwater streams to very large rivers, and includes floodplains and wetlands associated with channels. Literature suggests that ecosystem alteration by humans prior to and during Euro-American settlement changed from predominantly terrestrial to both terrestrial and freshwater in a manner that was time-transgressive with Euro-American colonization and U.S. settlement between the 17th and 19th centuries. The extent and intensity of post-Euro-American alteration of freshwater environments in the United States has resulted in widespread river metamorphosis toward more geomorphically and ecologically homogenous systems. Recognition of the rapidity and ubiquity of this alteration, and the consequent instability of many contemporary river corridors, should underpin contemporary river management.